Green Initiative: Community Outreach on the Cultivation and Sustainable Management of Potential Plant Species in Tumbang Habaon Village, Tewah Distric - Gusnia Devianti; Zimon Pereiz; Chuchita Chuchita; Efriyana Oksal; Mesra Ratna Sari Telaumbanua; Felly Sabatini; Julia J; Angelia Solla; Debby Catur Prasetyo; Gracyela Hutabalian; Anjelika A; Heja H; Ornella Arnia Florensia; Mauliya Apriyanti; Andika Prayoga; Arisumi Ir L Tundan, Jonathan Dandy; Abdullah A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Green Initiative conducted in Tumbang Habaon Village, Tewah District, Gunung Mas Regency, Central Kalimantan, aimed to improve environmental awareness and strengthen community capacity in the cultivation and sustainable management of potential plant species. Using a Participatory Action Research (PAR) approach, the program involved socialization activities, technical training, and the collaborative planting of 2,000 trees, including guava, petai, and jengkol. Community members received guidance on proper planting techniques, land preparation, and plant maintenance. The activity successfully increased community understanding of environmental conservation from 40% to 80%. The planted trees showed an 85% survival rate within the first six months, supported by routine mentoring. The program also generated early economic benefits for 50 households through the introduction of productive tree species and contributed to reducing flood risks and improving local biodiversity. Challenges faced during implementation—such as limited availability of quality seedlings and initial community reluctance—were addressed through cooperation with local government stakeholders. Overall, the Green Initiative serves as a practical community service model that promotes environmental sustainability, community participation, and local empowerment, with potential for replication in other rural villages facing similar environmental issues.